Research on structural design of exoskeleton assisted transport robot based on artificial intelligence - Dai, Xianglin; He, Xin; Zhang, Ling (Molecular & Cellular Biomechanics, 2025)
With the comprehensive docking of “Made in China 2025” and Industry 4.0, the handling mode of the handling system is constantly updated and developed, and a new handling mode which is assisted by exoskeletons and other equipment to complete the handling work is gradually applied. However, most of the existing exoskeleton assisted robots are expensive and complex in structure, and are not suitable for the actual needs of ordinary workers, so it is of great significance to design an exoskeleton assisted handling robot suitable for the needs of ordinary workers. Based on this, this paper designs a relatively simple structure, relatively low cost of exoskeleton assisted transport robot. The simulation analysis of the reliability of the robot is carried out, and the results show that the exoskeleton assisted robot designed in this paper has high reliability, and the force condition of carrying heavy objects is more matching with each joint of the human body.